Why Do We Hold Mixed Emotions About Racial Out-Groups? A Case for Affect Matching - Barlow, Fiona Kate; Hornsey, Matthew J.; Hayward, Lydia E.; Houkamau, Carla A.; Kang, Jemima; Milojev, Petar; Sibley, Chris G. (Psychological Science, 2019)
A four-wave survey on a national probabilistic sample ( N = 17,399) tested novel predictions about how positive and negative contact with racial out-groups predicts warmth and anger toward those groups. Three competing hypotheses were tested: (a) that negative contact will outweigh positive contact when predicting both emotions (“bad is stronger than good”); (b) that negative and positive contact will similarly predict each emotion; and (c) that negative contact will have a disproportionately large association with anger (a negative emotion), whereas positive contact will have a disproportionately large association with warmth (a positive emotion)—a phenomenon known as affect matching. The data revealed clear evidence for affect matching: Negative contact was associated with high levels of anger more than low levels of warmth, whereas positive contact was associated with high levels of warmth more than low levels of anger. Results suggest that positive and negative feelings about out-groups may be tied to qualitatively distinct contact experiences.